IDENTIFICATION OF RISK FACTORS FOR URINARY TRACT INFECTION IN PATIENTS WITH UROLITHIASIS - RIZWAN , A; SHAHJEHAN, .; GHOUS , G; ALI , W; GORAYA , IS; HANIF , U (Biological and Clinical Sciences Research Journal, 2023)
Urinary tract infections (UTIs) are common among patients with urolithiasis, making treatment complicated and even dangerous. This study aimed to identify risk factors associated with UTIs in urolithiasis patients. A retrospective study was conducted at Mayo Hospital Lahore, which included 300 patients with kidney stones. The patients were separated into two groups: those with UTIs and those without. Various factors were examined, including age, gender, smoking history, stone structure, alcohol use, stone location, and presence of blockages in the urinary tract. Out of the 300 patients, 73 (24.33%) had UTIs. The most common pathogens found in the urine cultures were gram-negative bacteria, followed by gram-positive bacteria and fungi. The study concluded that gender, age, blockages in the urinary tract, stone structure, and multiple stone locations could be considered independent risk factors for UTIs in urolithiasis patients. However, no statistically significant relationship was found between drinking and smoking and the incidence of UTIs. The most common organism found in UTIs among urolithiasis patients was a gram-negative bacillus.